Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I just ran into this:

$$\begin{align} x^1+y^1+z^1&=0\\ x^3+y^3+z^3&=3\\ x^4+y^4+z^4&=15\\ x^2+y^2+z^2&=\text{?} \end{align}$$

I know the answer, but can this be solved without guessing?

share|cite|improve this question
I see that $xyz=1$. – user21436 Mar 29 '12 at 22:09
If you can afford the CPU cycles, there's Grobner basis :) – user2468 Mar 29 '12 at 23:05
up vote 5 down vote accepted

Yes, this can be solved without guessing, using Newton's identities.

Since $x + y + z = 0$, they are the roots of $t^3 + at -b = 0$.

Newton's identities give us (in a straightforward mechanical manner) that

$$x^3 + y^3 + z^3 = 3b$$ $$x^4 + y^4 + z^4 = 2a^2$$

and $$x^2 + y^2 + z^2 = -2a$$

This gives us $b=1$ and $2a^2 = 15$.

You can solve for $a$ and find the value of $x^2 + y^2 + z^2 = -2a$. Note that if you assume $x,y,z$ are real, then you need to pick $a \lt 0$ which gives us

$$x^2 + y^2 + z^2 = \sqrt{30}$$

Note that you did not even need to use the value of $x^3 + y^3 + z^3$.

You can also derive the above identities in a slightly tedious way, as in my answer here: Simplifying an expression

share|cite|improve this answer
See Also:… – Aryabhata Mar 29 '12 at 22:27
Since $t^3+at-b=0$ substituting successively for $x,y,z$ and adding gives the first identity (noting $x+y+z=0$). Just a trick which helps sometimes - though the identities work best for a computer if you are programming. – Mark Bennet Mar 29 '12 at 22:36
@MarkBennet: Right! This is what I was referring to in the last link. – Aryabhata Mar 29 '12 at 22:38
please forgive my laziness ... – Mark Bennet Mar 29 '12 at 22:54
@MarkBennet: You don't have to apologize! That sentence isn't clear on what the different way is. Your comment helps clarify it a bit. In fact, I was the one being lazy... – Aryabhata Mar 29 '12 at 22:57

Note that $0 = (x+y+z)^2 = (x^2+y^2+z^2) + 2(xy+xz+yz)$, so $x^2+y^2+z^2 = -2(xy+xz+yz)$.

And $$\begin{align*} 15 &= x^4+y^4+z^4\\ & = (x^2+y^2+z^2)^2 - 2(x^2y^2 + x^2z^2 + y^2z^2).\end{align*}$$

And $$\begin{align*} (xy+xz+yz)^2 &= (x^2y^2 + x^2z^2 + y^2z^2) + 2(x^2yz+xy^2z+xyz^2)\\ &= (x^2y^2+x^2z^2 + y^2z^2) + 2xyz(x+y+z)\\ &= x^2y^2+x^2z^2+y^2z^2 + 2xyz(0)\\ &= x^2y^2+x^2z^2+y^2z^2 \end{align*}$$ hence $$x^2y^2+x^2z^2+y^2z^2 = (xy+xz+yz)^2.$$ So $$\begin{align*} 15 &= x^4+y^4+z^4\\ &= (x^2+y^2+z^2)^2 - 2(x^2y^2 + x^2z^2+y^2z^2)\\ &= (x^2+y^2+z^2)^2 - 2(xy+xz+yz)^2\\ &= (x^2+y^2+z^2)^2 -2(xy+xz+yz)(xy+xz+yz)\\ &= (x^2+y^2+z^2)^2 +(x^2+y^2+z^2)(xy+xz+yz)\\ &= (x^2+y^2+z^2)^2 + (x^2+y^2+z^2)\left(-\frac{1}{2}(x^2+y^2+z^2)\right)\\ &= (x^2+y^2+z^2)^2 -\frac{1}{2}(x^2+y^2+z^2)^2\\ &=\frac{1}{2}(x^2+y^2+z^2)^2 \end{align*}$$ so $(x^2+y^2+z^2)^2 = 30$, hence $x^2+y^2+z^2=\sqrt{30}$.

share|cite|improve this answer
This is just a pedestrian way of doing what Aryabhata notes. – Arturo Magidin Mar 29 '12 at 22:26
I'll +1 this answer for just the last comment. (You may know why, by now.) Amazing clarity as ever.+1 :-) – user21436 Mar 29 '12 at 22:31

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.